Peroxide-Mediated Alkyl-Alkyl Coupling of Dialkylzinc: A Useful Tool for Synthesis of ABA-Type Olefin Triblock Copolymers - Kim, Sung Dong; Kim, Tae Jin; Kwon, Su Jin; Kim, Tae Hee; Baek, Jun Won; Park, Hee Soo; Lee, Hyun Ju; Lee, Bun Yeoul (Macromolecules, 2018)
A practical and simple method for the preparation of ABA-type olefin triblock copolymers, e.g., PE-b-poly(ethylene-co-propylene)-b-PE, has been described. The performance of the so-called "coordinative chain transfer polymerization" (CCTP) by sequential feed of ethylene and ethylene/propylene mixed gas generated a Zn-bound diblock copolymer (i.e., (PE-b-poly(ethylene-co-propylene)yl)2Zn). Treatment of the Zn-bound diblock copolymer with lauroyl peroxide (CH3(CH2)10C(O)O-OC(O)(CH2)10CH3) led to a C(sp3)-C(sp3) coupling reaction between the two diblock chains bound on the zinc site and an ABA-type olefin triblock copolymer, PE-b-poly(ethylene-co-propylene)-b-PE, was formed. Upon the treatment with lauroyl peroxide, the number-average molecular weight increased by 1.5-1.7 times. The occurrence of the coupling reaction was verified using a model compound, (Oct)2Zn. The ABA-type triblock copolymer exhibited thermoplastic elastomeric properties and dramatically improved mechanical properties (twice the tensile strength and 10-fold increase in the elongation at break) as compared to the diblock congener.
Keywords: Chain transfer polymerization; Coupling reaction; Elastomeric properties; Elongation at break; Mixed gas; Model compound; Number average molecular weight; SIMPLE method